Neurological outcomes of extended thymectomy for thymomatous myasthenia gravis: Subxiphoid vs. trans-sternal approaches - Zhu, Haoshuai; Liu, Zhihao; Yao, Xiaojing; Zou, Jianyong; Zeng, Bo; Zhang, Xin; Chen, Zhenguang; Su, Chunhua (Frontiers in Surgery, 2022)
Background: The subxiphoid approach is widely utilized recently. However, few data focus on the neurological outcomes of patients with thymomatous myasthenia gravis (MG) receiving subxiphoid thoracoscopic thymectomy. The goal of this study is to compare the neurological outcomes of patients with thymomatous MG receiving extended thymectomy under subxiphoid approach or trans-sternal approach during a year postoperatively Methods: The records of patients with Masaoka stage I and II thymoma with tumor size less than 5 cm and thymomatous MG who underwent extended thymectomy from January 2019 to December 2020 were retrospectively reviewed and evaluated. The neurological outcomes were measured by Quantitative Myasthenia Gravis score (QMGs) with a reduction of QMGS of 2.3 points correlated with improved clinical MG status. Clinical efficacy and variable influencing outcomes were evaluated by Kaplan-Meier method and Cox proportional hazard regression analysis. Results: A total of 89 patients were included in analysis, of which 44 in the subxiphoid approach and 45 in the trans-sternal approach. The mean QMGs decreased from 12 at initial diagnosis to 8.7 preoperatively, to 5.6 at 12-mon postoperatively in the subxiphoid group, and from 12.1 to 8.9, to 6.0 in the trans-sternal group. 13 patients (28.9%) in trans-sternal approach and 10 patients (22.7%) in subxiphoid approach did not get improved clinical status from preoperative time. The median time to a get improved clinical status was 3 months (95% CI: 2.15-3.85) in subxiphoid approach and 6 months (95% CI: 5.54-6.46) in trans-sternal approach. Univariable results indicate that subxiphoid approach was associated with faster improved clinical status (HR=1.701, 95%CI: 1.044-2.773, p<0.05), and age ≦48 was associated with faster improved clinical status (HR=1.709, 95%CI: 1.044-2.799, p<0.05). Age ≦48 (HR= 1.837, 95%CI: 1.093-3.086, p=0.022) and subxiphoid approach (HR=1.892, 95%CI: 1.127-3.177, p=0.016) were significant associated with faster improved clinical stasus in multivariable model. Conclusions: In patients with Masaoka stage I and II thymoma with tumor size less than 5 cm and thymomatous MG who receive thymectomy, age ≦48 years and subxiphoid approach are associated with faster improved clinical status.